Reconstruction of cervico-thoracic defect with bipedicled deep inferior epigastric perforator free flap following resection of a giant recurrent thyroid tumor: a case report and review of literature - Zavala, A (2023)
The bipedicled Deep Inferior Epigastric Perforator (DIEP) flap, originally described and primarily utilized in autologous breast reconstruction for specific cases, has expanded its applications to encompass diverse anatomical regions in recent years. This report presents the case of a 69-year-old woman with a recurrent giant thyroid tumor who underwent surgical resection, resulting in a large cervico-thoracic defect effectively reconstructed using a bipedicled DIEP flap. The patient's postoperative recovery was uneventful, and the follow-up assessments revealed a healthy, well-perfused flap that provided sufficient coverage to critical structures, adequate restoration of the region contour, and enough volume to offset potential adverse effects of subsequent radiation therapy. In addition, this report incorporates a concise literature review highlighting the expanding indications of the bipedicled DIEP flap beyond breast reconstruction, showing the versatility and efficacy of the bipedicled DIEP flap in addressing complex soft-tissue defects in various anatomical areas.